Vehicle Routing for Infectious Healthcare Waste Collection With Transit Points: A Problem Incorporating Multiple Types of Risks and Two Solution Methods From Different Perspectives - Meng Zhang; Wei Cui; Qi Jiang; Nengmin Wang; Yuan Shang (IEEE Access)
Infectious healthcare waste is a kind of high-risk material. With the continuous outbreak of infectious diseases in recent years, infectious healthcare waste collection (IHWC) has garnered significant attention. As infectious healthcare waste volume has increased substantially, many countries have chosen to incorporate transit points into their IHWC process to leverage consolidation effects. Besides, transporting infectious healthcare waste involves transport risks, and the storage of such waste at medical institutes and transit points also poses storage risks. In this paper, a vehicle routing problem for IHWC with multiple types of risks and transit points (VRP for IHWC-MR-TP) is proposed, considering the complexity introduced by the simultaneous existence of transport risks, storage risks, and transit points, and aiming to simultaneously minimize the total cost and the maximum risk. A bi-objective model of VRP for IHWC-MR-TP is developed. Based on the characteristics of the problem, two different solution methods are proposed, including a global solution method from a global perspective and a two-stage solution method that divides the problem into two stages for optimization. The model and solution methods are tested through numerical experiments. The results indicate that compared to the global solution method, the two-stage solution method can reduce the solving time by an average of 26.6%, while decreasing the Hypervolume by only an average of 0.5%. Finally, managerial insights are derived through sensitive analysis. The results demonstrate that an increase in collection vehicle speed results in lower cost and risk, therefore decision-makers should pay attention to vehicle maintenance and driver training in normal operations to ensure that relatively high vehicles’ speeds can be maintained during IHWC. Furthermore, as the capacities of vehicles increase, both cost and risk demonstrate a significant downward trend, suggesting that decision-makers should choose vehicles with larger capacities for IHWC.